Soluble fas levels correlate with multiple organ dysfunction severity, survival and nitrate levels, but not with cellular apoptotic markers in critically ill patients - Papathanassoglou, Elizabeth; Moynihan, Jan; Vermillion, Dianne (My University, 2000)
Apoptosis is a mode of programmed cell death (PCD). Transduction of apoptotic signals results in cellular suicide. Organ specific apoptosis has been proposed as a factor in multiple organ dysfunction syndrome (MODS). Fas is a widely occurring apoptotic signal receptor molecule expressed by almost any type of cell, which is also released in a soluble circulating form (circulating fas, sfas). In this exploratory study, we investigated the association of sfas with severity, survival, known mediators of multiple organ dysfunction, and cellular apoptotic markers on peripheral blood mononuclear cells (PBMC) in a group of 35 patients with MODS and in 35 matched controls. Critically ill patients with MODS had significantly elevated sfas levels compared to controls over time (P < .001). Increased serum concentration of circulating fas was associated with increased severity of multiple organ dysfunction. Non-survivors exhibited significantly higher sfas levels compared to survivors (P < .01) and increasing sfas was inversely associated with the likelihood of survival (P < .05). Circulating fas levels correlated highly with serum nitrate concentration, but not with fas and fasL expression on PBMC of critically ill patients. TNF-α and IL-6, although they appear to be mediators of both apoptosis and MODS, had no association with sfas. These results are suggestive of the need for further investigation on the role of apoptotic signaling in the development of MODS. They also suggest a potential prognostic value of sfas for SIRS/MODS clinical outcomes
Keywords: Shock; Apoptosis; Cytokines; Multiple organ failure; Tumor necrosis factor; Catastrophic illness